The role of macrophages in anti-inflammatory activity of antidepressant drugs - Nazimek, Katarzyna; Strobel, Spencer; Bryniarski, Paweł; Kozlowski, Michael; Filipczak-Bryniarska, Iwona; Bryniarski, Krzysztof (Immunobiology (1979), 2017)
[Display omitted] Depression is a common disease influencing patients’ quality of life, whose etiology involves complex interactions of environmental, genetic and immunological factors. The latter factors include proinflammatory activation of monocytes and macrophages and increased serum levels of proinflammatory cytokines, altogether formulated as the “macrophage theory of depression”. Our current review summarizes the impact of the most commonly used antidepressant drugs on the immune response with special emphasis on the role of macrophages in the clinically observed effects. The anti-inflammatory action of antidepressants mainly results from their direct interaction with immune cells and from changes in the concentration and the relations of neurotransmitters sensed by these cells. The summarized data revealed that Mφs are one of the leading cell populations involved in drug-mediated immune effects that can be observed both in subjects with depression as well as in individuals not suffering from depression. Thus, currently reviewed immunomodulatory effects of the experimental use of different antidepressant drugs suggest the possibility of utilizing them in complex therapeutic strategies dedicated to various inflammatory and immune-mediated diseases. It is worth noting that an excessive inflammatory reaction is also associated with the pathogenesis of various cardiovascular, metabolic and neuro-endocrine diseases. Thus, the inclusion of antidepressants in the complex therapy of these disorders may have beneficial effects through the enhancement of the mood of the patient and alleviation of chronic inflammation. On the other hand, presented data suggest that the influence of chronically used antidepressants on anti-microbial and anti-tumor immunity could also be taken into consideration.